Multi-time-scale X-ray reverberation mapping of accreting black holes. Issue 3 (10th January 2018) - Mastroserio, Guglielmo; Ingram, Adam; van der Klis, Michiel
Abstract: Accreting black holes show characteristic reflection features in their X-ray spectrum, including an iron Kα line, resulting from hard X-ray continuum photons illuminating the accretion disc. The reverberation lag resulting from the path-length difference between direct and reflected emission provides a powerful tool to probe the innermost regions around both stellar-mass and supermassive black holes. Here, we present for the first time a reverberation mapping formalism that enables modelling of energy-dependent time lags and variability amplitude for a wide range of variability time-scales, taking the complete information of the cross-spectrum into account. We use a pivoting power-law model to account for the spectral variability of the continuum that dominates over the reverberation lags for longer time-scale variability. We use an analytic approximation to self-consistently account for the non-linear effects caused by this continuum spectral variability, which have been ignored by all previous reverberation studies. We find that ignoring these non-linear effects can bias measurements of the reverberation lags, particularly at low frequencies. Since our model is analytic, we are able to fit simultaneously for a wide range of Fourier frequencies without prohibitive computational expense. We also introduce a formalism of fitting to real and imaginary parts of our cross-spectrum statistic, which naturally avoids some mistakes/inaccuracies previously common in the literature. We perform proof-of-principle fits to Rossi X-ray Timing Explorer data of Cygnus X-1.